2014
DOI: 10.2147/ppa.s55483
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in elderly patients following coronary artery bypass grafting

Abstract: BackgroundSurgical revascularization of the coronary arteries leads to changes in quality of life (QoL) for patients with coronary heart disease. The aim of this work was to monitor QoL, considering cognitive function, depression, and activities of daily living in elderly patients after coronary artery bypass grafting (CABG).MethodsThis study included 65 patients (29 women and 36 men) aged 61–74 years with stable coronary heart disease who underwent CABG. The control group included 29 women and 36 men aged 61–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
4
8
0
2
Order By: Relevance
“…Our study confirmed that patients developed POD after CABG was associated with almost fivefold increase in developing cognitive impairment even at 18 months after discharge, and cognitive function had a medium‐to‐large effect on QoL after discharge. Our findings are consistent with previous studies (Bak & Marcisz, ; Khadka et al, ; Rothenhausler et al, ; Steinmetz et al, ). However, we found that POD had no direct effect on QoL after discharge, while the QoL of patients who developed POD after CABG was determined by the presence of cognitive function decline.…”
Section: Discussionsupporting
confidence: 94%
“…Our study confirmed that patients developed POD after CABG was associated with almost fivefold increase in developing cognitive impairment even at 18 months after discharge, and cognitive function had a medium‐to‐large effect on QoL after discharge. Our findings are consistent with previous studies (Bak & Marcisz, ; Khadka et al, ; Rothenhausler et al, ; Steinmetz et al, ). However, we found that POD had no direct effect on QoL after discharge, while the QoL of patients who developed POD after CABG was determined by the presence of cognitive function decline.…”
Section: Discussionsupporting
confidence: 94%
“…The variables of myocardial infarction and bypass surgery, which are specific for the cardiac population, did not show associations with suicidal ideation. Regarding bypass surgery, this result is consistent with studies showing considerable improvement in quality of life in patients after bypass surgery (Bak & Marcisz, ; Baron et al, ; Kulik, ; Peric et al, ). Finally, suicidal patients show higher scores on standardized clinical scales and on scales related to heart disease (i.e., shortness of breath and chest pain).…”
Section: Discussionsupporting
confidence: 89%
“…In other words, results indicated that the quality of life and its emotional, physical, and social aspects were improved in the patients of the intervention group after theorybased educational intervention, which was statistically significant (p<0.05). In this regard, our findings are in line with the results obtained by Bak [18] , Mathisen et al [19] , and Hunt et al [21] . In a research by Lindsay et al [22] , all aspects of quality of life were improved in patients after the implementation of rehabilitation programs, where education played a significant role.…”
Section: Discussionsupporting
confidence: 94%
“…The health promotion model is designed based on Bandura's social recognition theory, health belief model, and Pender's studies on healthpromoting behaviors and self-care. In addition, the efficiency of this model has been confirmed by various studies [18,19] . However, no research has been carried out on the efficiency of this model to promote the quality of life of cardiac patients.…”
Section: Introductionsupporting
confidence: 55%